Glycemic control and self-rated health among ethnically diverse adolescents with type 1 diabetes - Kane, Naomi S. (Pediatr Diabetes, 2019)
OBJECTIVE: Patient-reported outcomes have received increased attention as treatment outcomes and indicators of wellbeing. A1c has been criticized as lacking patient-centered relevance because individuals are often unaware of their A1c, and studies also often fail to show a benefit of intensive control on quality of life. The goal of the present study was to examine self-rated health (SRH) in relation to diabetes self-care behaviors, socioeconomic factors, treatment regimen characteristics, and glycemic control among predominately Hispanic and African American adolescents with type 1 diabetes (T1D). METHODS: Adolescents with T1D (N = 84) were recruited for a cross-sectional study evaluating psychosocial factors and identity development. SRH, self-care behaviors, treatment regimen, and demographic variables were collected through self-report while glycemic control (A1c) was determined through chart review. RESULTS: Participants were predominantly racial and ethnic minorities (48% Hispanic, 27% African American; 52% female, M age 15.9, M diabetes duration 6.8, M A1c 10% [86 mmol/mol]). Significant bivariate relationships emerged between SRH and sex, A1c, self-care behavior, and insulin delivery method. Covariate-adjusted regression models showed only A1c was significantly and independently related to SRH. Mediation analyses illustrated a significant indirect effect for A1c between self-care and SRH. CONCLUSION: These findings suggest glycemic control is associated with self-ratings of health among ethnically diverse adolescents with T1D. SRH appears to be an appropriate patient-reported outcome that is sensitive to glycemic control in this population.